THE ADAPTIVE SMOOTHING FILTERS OF SENSOR SIGNALS IN THE MICROAVIONIC SYSTEMS - V. A. Malkin (Приборы и методы измерений)
The adaptive for intensivity of measuring noise filters for smooth of sensor signals are considered. The adaptation are realized at the expense of the statistical processing of the filtering errors. The algorithm of adaptive filter coefficients calculation and modeling results are presented.